Penggunaan Internet dalam Mengubah Peradaban Manusia - Fatmawati Sungkawaningrum; Najib Mubarok (Jurnal Ilmiah Citra Ilmu : Kajian Kebudayaan dan Keislaman, 2020)
The internet has a different character from the real world. In choosing what content is needed via the internet, sometimes it becomes uncontrollable because of the wrong tendency to use the internet. From the internet, a lot of what is offered can be a positive influence and can be a negative influence. The heart gets orders from the brain to carry out an activity. Many academicians have dropped out of online gaming. Work that should be done, but not done. Activity targets that have been determined are not implemented. Humans are equipped with feelings, ambitions, abilities, fear, feelings of rebellion, a sense of compulsion. All of these are very useful for the management of our anatomical structures. Whatever happens is the source of what has become the habit of a group of humans. Humans are learned by other human groups to make an income field in it. This research method uses an Islamic economic approach that uses time effectively and efficiently. Data collection techniques with observations in the STAINU Temanggung area. The purpose of this study is that everyone understands the positive and negative effects of internet use. The result of this research is that the internet changes the pattern of life, starting from the behavior of human resources, and the systems used. Among them are in the social, cultural, economic, and positive mindset and some are negative. We are unlikely to reject or even be hostile to it, but we are required to be obliged to manage it wisely.